Cornual pregnancy-an unusual site of pregnancy: a case report and literature review (BIRDEM Medical Journal, 2019)
Ectopic pregnancy is a condition where gestational sac is located outside the uterine cavity. Cornual pregnancy, also known as interstitial pregnancy, is a rare type of ectopic pregnancy that develops in the interstitial portion of the fallopian tube and invades through the uterine wall. It poses great diagnostic challenge because of its unusual presentation and late diagnosis. Cornual pregnancy, if not diagnosed early, may present with massive and uncontrollable bleeding even leading to maternal death. We hereby report an unusual presentation of cornual pregnancy which was diagnosed and subsequently managed successfully.Birdem Med J 2020; 10(1): 64-67